Advances in water disinfection by photocatalysis - Zhang, L.; Wong, P.K. (Progress in Nutrition, 2011)
SummaryAn AgBr-Ag-Bi2WO6 nanojunction was synthesized by a facile deposition-precipitation method. Two VL-active components (AgBr and Bi2WO6) and the electron-transfer component (Ag) were spatially fixed in this nanojunction system. The VLD photocatalytic disinfection of E. coli K-12 by the AgBr-Ag-Bi2WO6 nanojunction, which could completely inactivate 5×107 cfu mL-1 of bacterial cells within 15 min, was greatly superior to other reported VLD photocatalysts. The mechanism of VLD photocatalytic disinfection was also investigated. It was found that the diffusing •OH, generated by both the oxidative and the reductive pathways of photocatalysis, was the major reactive species to inactivate bacterial cells, and that the direct contact between the AgBr-Ag-Bi2WO6 nanojunction and the bacterial cells was not required.I progressi nella disinfezione dell’acqua attraverso la fotocatalisiRiassuntoUna nanogiunzione AgBr-Ag-Bi2WO6 è stata sintetizzata con un facile metodo di deposizione-precipitazione. Due componenti VL-attivi (AgBr e Bi2WO6) e il componente donatore di elettroni (Ag) sono stati fissati spazialmente in questo sistema di nanogiunzione. La disinfezione fotocatalitica VLD di E. coli K-12 da parte della nanogiunzione AgBr-Ag-Bi2WO6, che potrebbe inattivare completamente 5×107 ufc ml-1 di cellule batteriche in 15 minuti, è risultata di gran lunga superiore ad altri fotocatalizzatori VLD riportati. In questo lavoro è stato anche analizzato il meccanismo di disinfezione fotocatalitico VLD. Si è scoperto che gli •OH diffusi, generati sia dal pathway ossidativo che riduttivo della fotocatalisi, erano la principale specie reattiva ad inattivare le cellule batteriche e che non era richiesto il contatto diretto tra la nanogiunzione AgBr-Ag- Bi2WO6 e le cellule batteriche.